Effect of finite wall thickness on entropy generation and natural convection in a nanofluid-filled partially heated square cavity - Ishak M.S.; Alsabery A.I.; Chamkha A.; Hashim I. (Emerald Publishing, 2023)
Alumina; Aluminum oxide; Entropy; Finite difference method; Isotherms; Nanofluidics; Numerical methods; Thermal conductivity; Entropy generation; Entropy generation analysis; Finite wall thickness; Heat sources; Horizontal walls; Nanofluids; Solid wall; Square cavity; Wall thickness; Water nanofluids; Natural convection